2019
DOI: 10.4274/jtgga.galenos.2018.2018.0124
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-step ligation of the internal iliac artery

Abstract: The internal iliac artery is the main vascular supply of pelvic visceral structures. All pelvic surgeons must know the anatomic landmarks and basic steps of internal iliac artery ligation in order to stop massive pelvic hemorrhage. This cadaveric demonstration and clinical review of the internal iliac artery shows the anatomic landmarks and basic steps of internal iliac artery ligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Bilateral internal iliac artery (IIA) ligation is a life-saving procedure which significantly reduces the pulse pressure and rate of blow flow caused by a hemorrhage, subsequently allowing effective thrombosis within small bleeding vessels, such as the OA [ 37 ]. After ligation, the pubic branches of the obturator artery anastomose with the inferior epigastric artery, a branch of the external iliac artery [ 38 ]. Some different indications regarding the IIA ligation are uterine laceration during endovascular repair of aortoiliac arterial aneurysm, radical hysterectomy or exenteration, postpartum hemorrhage secondary to abruption or placenta previa, and—as stated earlier—profuse pelvic hemorrhage from fracture of the pelvis or gunshot injury to the pelvis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral internal iliac artery (IIA) ligation is a life-saving procedure which significantly reduces the pulse pressure and rate of blow flow caused by a hemorrhage, subsequently allowing effective thrombosis within small bleeding vessels, such as the OA [ 37 ]. After ligation, the pubic branches of the obturator artery anastomose with the inferior epigastric artery, a branch of the external iliac artery [ 38 ]. Some different indications regarding the IIA ligation are uterine laceration during endovascular repair of aortoiliac arterial aneurysm, radical hysterectomy or exenteration, postpartum hemorrhage secondary to abruption or placenta previa, and—as stated earlier—profuse pelvic hemorrhage from fracture of the pelvis or gunshot injury to the pelvis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantages, in patients with obesity and a large uterus, the approach becomes difficult. 5 This educational video demonstrates the relevant anatomic structures and key points involved in the ligation technique for the internal iliac artery. It aims to enlighten the residents and pelvic surgeons.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In obstetric bleeding HA, ligation can decrease pelvic arterial blood supply and pressure as much as 58 and 85%, consecutively. 13 Refaie et al reported that appropriate hemostasis can be observed in 82.4% of the patients treated with HA ligation. 7 Yildiz et al also found that 15 patients with the adhesive placenta and placenta previa that were treated with HA ligation and hysterectomy had a similar outcome with patients Journal of South Asian Federation of Obstetrics and Gynaecology, Volume 14 Issue 3 (May-June 2022) that were treated without hysterectomy.…”
Section: Introductionmentioning
confidence: 98%